"No more plastic balls": Symbolic childhoods in Zimbabwean short stories of the crisis. (September 2018) - Nyambi, Oliver
Post-2000 Zimbabwean literature in English demonstrates an unprecedented fascination with the child narrator. While there is some precedence for the use of child narrators or narratives that focus on child experiences to grapple with sociopolitical issues, the wide extent to which this style has been used post-2000 is unparalleled. The post-2000 socioeconomic crisis in Zimbabwe has clear victims; however, owing to the intensely polarized perspectives on its origins and nature, the identity of the victimizers is not so clear and is in fact hotly contested and politicized. As typical and "known" victims, their victimization can furtively reveal and reflect on their victimizers and in the process subtly expose them for knowing. This form of "knowing" transcends a mere discernment of the victimizers' physical identities; it goes to the heart of their motives, apparent and subterranean political objectives, and means of attaining them. Victim child characters are often used symbolically to represent the weak and vulnerable members of society who are exploited as political fodder by the powerful. The symbolic children are seen to be caught in between the political goals and strategies of the powerful, and their victimization reveals overt and covert markings of their political abuse. This makes child-narrated or child-centred narratives possible sites to encounter the nexus between children's victimization and the underhand methods of creating and sustaining political hegemony. This article explores this connection, particularly focusing on the aesthetic subtlety with which child-centred or child-focused narratives proffer a counter-discursive discourse which unsettles the dominant narratives presently given of victims and victimizers in a post-2000 Zimbabwean context.